Associations between deduced first islet specific autoantibody with sex, age at diagnosis and genetic risk factors in young children with type 1 diabetes - Ilonen Jorma; Laine Antti-Pekka; Kiviniemi Minna; Härkonen Taina; Lempainen Johanna; Knip Mikael (WILEY, 2022)
Objectives We aimed to further characterize demography and genetic associations of type 1 diabetes "endotypes" defined by the first appearing islet specific autoantibodies. Research Design and Methods We analyzed 3277 children diagnosed before the age of 10 years from the Finnish Pediatric Diabetes Register. The most likely first autoantibody could be deduced in 1636 cases (49.9%) based on autoantibody combinations at diagnosis. Distribution of age, sex, HLA genotypes and allele frequencies of 18 single nucleotide polymorphisms (SNPs) in non-HLA risk genes were compared between the endotypes. Results Two major groups with either glutamic acid decarboxylase (GADA) or insulin autoantibodies (IAA) as the deduced first autoantibody showed significant differences in their demographic and genetic features. Boys and children diagnosed at young age had more often IAA-initiated autoimmunity whereas GADA-initiated autoimmunity was observed more frequently in girls and in subjects diagnosed at an older age. IAA as the first autoantibody was also most common in HLA genotype groups conferring high-disease risk while GADA first was seen more evenly and frequently in HLA groups associated with lower type 1 diabetes risk. The risk alleles in IKZF4 and ERBB3 genes were associated with GADA-initiated whereas those in PTPN22, INS and PTPN2 genes were associated with IAA-initiated autoimmunity. Conclusions The results support the assumption that in around half of the young children the first autoantibody can be deduced based on islet autoantibody combinations at disease diagnosis. Strong differences in sex and age distributions as well as in genetic associations could be observed between GADA- and IAA-initiated autoimmunity.